1998
DOI: 10.1073/pnas.95.17.9779
|View full text |Cite
|
Sign up to set email alerts
|

PDZ-domain-mediated interaction of the Eph-related receptor tyrosine kinase EphB3 and the ras-binding protein AF6 depends on the kinase activity of the receptor

Abstract: Eph-related receptor tyrosine kinases (RTKs) have been implicated in intercellular communication during embryonic development. To elucidate their signal transduction pathways, we applied the yeast two-hybrid system. We could demonstrate that the carboxyl termini of the Eph-related RTKs EphA7, EphB2, EphB3, EphB5, and EphB6 interact with the PDZ domain of the ras-binding protein AF6. A mutational analysis revealed that six C-terminal residues of the receptors are involved in binding to the PDZ domain of AF6 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
170
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(175 citation statements)
references
References 30 publications
4
170
1
Order By: Relevance
“…However, LTS2 could neither interact with the Omi PDZ domain nor be cleaved by STS-activated Omi protease under our experimental conditions (Supplementary Information, Figure S9, S10). Recent analysis of target specificity between the PDZ domain and its binding partner has demonstrated that like the extreme C-terminal three peptides the residues at positions -1, -4 and/or -5 of ligands are important for many PDZ interactions (Songyang et al, 1997;Hock et al, 1998). Given that amino acids at positions -4 and -5 of LTS2 differ from the corresponding locations on WTS (WTS: Arg-AspLeu-Val-Tyr-Val; LTS2: Cys-Gln-Pro-Val-Tyr-Val), the interaction is specific for WTS.…”
Section: Discussionmentioning
confidence: 99%
“…However, LTS2 could neither interact with the Omi PDZ domain nor be cleaved by STS-activated Omi protease under our experimental conditions (Supplementary Information, Figure S9, S10). Recent analysis of target specificity between the PDZ domain and its binding partner has demonstrated that like the extreme C-terminal three peptides the residues at positions -1, -4 and/or -5 of ligands are important for many PDZ interactions (Songyang et al, 1997;Hock et al, 1998). Given that amino acids at positions -4 and -5 of LTS2 differ from the corresponding locations on WTS (WTS: Arg-AspLeu-Val-Tyr-Val; LTS2: Cys-Gln-Pro-Val-Tyr-Val), the interaction is specific for WTS.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, we assessed if the PDZ-domain protein AF6 could bind the intracellular domain of JAGGED1, since AF6 was previously reported to interact with six residues (RMEYIV) found at the C terminus of Jagged1 using a directed yeast two-hybrid analysis (13). Furthermore, AF6 is the mammalian homolog of Drosophila canoe which has been genetically linked to the Notch pathway (46).…”
Section: Fig 5 An Intact Pdz-ligand Is Required For Activation Of Thementioning
confidence: 99%
“…3A) (13). To determine if these residues were required for transformation by JAGGED1, we generated a mutant that has a deletion of the six C-terminal residues that comprise the PDZ-ligand (J1 ⌬PL ).…”
Section: Deletion Of Either the Extracellular Or Intracellular Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction inhibits the Ras-MAPK pathway and plays important roles in growth cone collapse, cell repulsion and morphogenesis of capillary endothelium. The C-terminal PDZ-binding motif of Eph receptors mediates their interactions with many neuronal PDZ scaffolding proteins, such as glutamate receptor interacting protein (GRIP), protein interacting with C-kinase (PICK1) and AF-6 [4,39,42,81]. Forward signaling through Eph receptors induces changes to the local milieu either through modulating actin dynamics or through the localization of scaffolding molecules in lipid rafts.…”
Section: The Forward and Reverse Signalingmentioning
confidence: 99%